2019
DOI: 10.1126/science.aap8628
|View full text |Cite
|
Sign up to set email alerts
|

Impact craters on Pluto and Charon indicate a deficit of small Kuiper belt objects

Abstract: The flyby of Pluto and Charon by the New Horizons spacecraft provided highresolution images of cratered surfaces embedded in the Kuiper belt, an extensive region of bodies orbiting beyond Neptune. Impact craters on Pluto and Charon were formed by collisions with other Kuiper belt objects (KBOs) with diameters from ~40 kilometers to ~300 meters, smaller than most KBOs observed directly by telescopes. We find a relative paucity of small craters ≲13 kilometers in diameter, which cannot be explained solely by geol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
166
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 140 publications
(176 citation statements)
references
References 90 publications
6
166
0
Order By: Relevance
“…We found that the large objects have a significant effect on long-term time scales, leading to a modest enhancement of the injection rate of new comets into the inner solar system. The reservoir requirements implied by our injection rate remain in broad agreement with recent reservoir estimations done from observations of the trans-Neptunian regions, as well as with those estimated from the analysis of cratering records on Pluto and 2014 MU 69 (Greenstreet et al 2015(Greenstreet et al , 2019Singer et al 2019).…”
Section: Introductionsupporting
confidence: 89%
“…We found that the large objects have a significant effect on long-term time scales, leading to a modest enhancement of the injection rate of new comets into the inner solar system. The reservoir requirements implied by our injection rate remain in broad agreement with recent reservoir estimations done from observations of the trans-Neptunian regions, as well as with those estimated from the analysis of cratering records on Pluto and 2014 MU 69 (Greenstreet et al 2015(Greenstreet et al , 2019Singer et al 2019).…”
Section: Introductionsupporting
confidence: 89%
“…population in collisional equilibrium (e.g., Dohnanyi 1969), while a steeper slope may indicate that the ISO population is fed partially by additional fragmentation events, such as tidal disruption (Bolin et al 2018;Raymond et al 2018a;Zhang & Lin 2020). In any case, the existence of subkilometer interstellar comets like 1I suggests that the size distribution of objects in extrasolar Kuiper Belts, the progenitors of extrasolar comets, is not truncated at 1-2 km, challenging the claim that the size distribution of objects in the solar system's Kuiper Belt is effectively truncated at 1-2 km in diameter (Singer et al 2019). The arrival of additional ISOs will provide further constraints on their physical properties and size distribution, enhancing our understanding of comets in extrasolar systems.…”
Section: Discussionmentioning
confidence: 98%
“…As a consequence of these scattering events, the inner super-Earth systems are destroyed and only a very small fraction of the systems formed in our simulations harbour inner super-Earths and outer gas giants. Schlecker et al (2020) studied the super-Earth -cold Jupiter relation as well, but used instead 300m planetesimals for the growth of their planetary embryos, not in agreement with the evidence in the solar system (Bottke et al 2005;Morbidelli et al 2009;Singer et al 2019;Stern et al 2019). However, they recover a similar result regarding the eccentricity of outer gas giants and surviving inner super-Earths.…”
Section: Discussionmentioning
confidence: 99%